2014
DOI: 10.1007/s10278-014-9751-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Referring Physician’s Clinical History and Indication as a Means for Communicating Chronic Conditions That Are Pertinent at the Point of Radiologic Interpretation

Abstract: The clinical history and indication (CHI) provided with a radiological examination are critical components of a quality interpretation by the radiologist. A patient's chronic conditions offer the context in which acute symptoms and findings can be interpreted more accurately. Seven pertinent (potentially diagnosis altering) chronic conditions, which are fairly prevalent at our institution, were selected. We analyze if and how in 140 CHIs there was mention of a patient's previously reported chronic condition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Clinical history is a critical component of image interpretation, and lack thereof may negatively affect the quality of interpretation [22]. The clinical history for imaging studies is currently indicated by ICD-9-CM codes, which are required to obtain appropriate reimbursement.…”
Section: Improve Clinical History Obtained With Imaging Studiesmentioning
confidence: 99%
“…Clinical history is a critical component of image interpretation, and lack thereof may negatively affect the quality of interpretation [22]. The clinical history for imaging studies is currently indicated by ICD-9-CM codes, which are required to obtain appropriate reimbursement.…”
Section: Improve Clinical History Obtained With Imaging Studiesmentioning
confidence: 99%
“…Physicians may also enter incomplete or conflicting information, adversely impacting communication to radiologists, interpretation quality, and quality of patient care. 2,3 Although redundancies may potentially add reliability and safety in collaborative work, 4 reducing redundant data entry is a goal in efforts to improve usability, efficiency, accuracy, and safety in order entry and clinical decision support (CDS) tools. [5][6][7] Despite multiple data entry, in a survey of radiologists, 72% reported not receiving enough clinical information about patients, and 87% reported that more information could lead to a change in study interpretation.…”
Section: Background and Significancementioning
confidence: 99%
“…Although they often receive vague or incomplete information, radiologists typically prefer more clinical information in order to focus on regions corresponding to given symptoms and to adjust their indices of suspicion. [4][5][6] However, it is also possible that providing information biases radiologists to overcall ambiguous findings or overlook findings elsewhere. Few data exist to guide practice in this common clinical scenario.…”
Section: Introductionmentioning
confidence: 99%